A case of trichilemmal cyst - Chunchan ZHENG; Sujun LUO; Ruitao ZOU; Guiyue CAI; Xiaoxuan CHEN; Na WEI; Rongyi CHEN (Pifu-xingbing zhenliaoxue zazhi, 2023)
A case of trichilemmal cysts is reported. A 31-year-old man presented with a 5-year history of nodule on his back with enlargement, pain and itching for 1 month. Dermatological examination showed erythema and erythematous plaques scattered on the trunk and extremities, covered with a small amount of silvery white scales. A demarcated exophytic tumor sized 2 cm×3 cm in dark red color was seen on the back, with telangiectasia on the surface. The tumor was slightly soft and tenderness (+) with poor mobility. No erosion or ulceration was observed. Histopathological examination showed a dermal cyst, which wall was composed of stratified squamous cells, and the content of cyst was keratin with focal calcification. The patient was diagnosed with trichilemmal cyst. Complete resection was given. No recurrence was observed over 4 months of follow-up.